2005
DOI: 10.1007/s10531-004-9662-x
|View full text |Cite
|
Sign up to set email alerts
|

Species richness coincidence: conservation strategies based on predictive modelling

Abstract: The present-day geographic distribution of individual species of five taxonomic groups (plants, dragonflies, butterflies, herpetofauna and breeding birds) is relatively well-known on a small scale (5 Â 5 km squares) in Flanders (north Belgium). These data allow identification of areas with a high diversity within each of the species groups. However, differences in mapping intensity and coverage hamper straightforward comparisons of species-rich areas among the taxonomic groups. To overcome this problem, we mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 54 publications
(53 reference statements)
2
33
3
Order By: Relevance
“…Furthermore, they found a high degree of congruence among the patterns of the different groups. The major difference between the results of Maes et al (2005) and our study is that they did not find any of the incorporated climatic variables to be of much importance. However, we found that for the herpetofauna the duration of sunshine was strongly negatively correlated with the number of species.…”
Section: Discussioncontrasting
confidence: 95%
See 2 more Smart Citations
“…Furthermore, they found a high degree of congruence among the patterns of the different groups. The major difference between the results of Maes et al (2005) and our study is that they did not find any of the incorporated climatic variables to be of much importance. However, we found that for the herpetofauna the duration of sunshine was strongly negatively correlated with the number of species.…”
Section: Discussioncontrasting
confidence: 95%
“…Only for herpetofauna diversity the environmental heterogeneity variables (heterogeneity of habitat or soil types and range in altitude) were not entered at an early stage in the stepwise modelling procedure. In general, these findings agree very well with the work of Maes et al (2005), who studied the species richness patterns of partly the same taxonomic groups in Belgium. They found that for all studied groups (plants, dragonflies, herpetofauna, butterflies and birds) the number of species was positively correlated with biotope diversity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although species richness has been considered a good surrogate of biodiversity in many studies (Real et al 1993;Araújo 1999;Maes et al 2005), there are some authors who have shown that species richness is more related with the distribution of generalist species than to the distribution of rare ones (Vázquez and Gaston 2004). However, the majority of the fuzzy favourability hotspots for mammals obtained in this study coincide with those of fuzzy mammal rarity in Andalusia (Real et al 2006b).…”
Section: Surrogates Of Biodiversitymentioning
confidence: 54%
“…Maes et al (2005) recommended that policy makers should make more use of modelling techniques as a proactive conservation tool, because it allows to better target sites predisposed to be included to a natural reserve network. In the same way, Ferrier (2002) proposed integrating biological and environmental data through predictive modelling as a strategy that may help alleviate some of the problems associated with using remotely mapped surrogates in conservation planning.…”
Section: Fuzzy Favourability Hotspotsmentioning
confidence: 99%